Growth, optical and structural characterization of InP nanostructures with In0.4Ga0.6P insertion layer. - Han, Soe Soe (Asean Engineering Journal)
Quantum dots in InP/GaAs system were grown by low pressure MOVPE via the Stranski-Krastanow growth mode. In order to control the dots diameter and improve the size uniformity and photoluminescence (PL) emission, the ternary In0.4Ga0.6P layers thickness (0-4) monolayers (MLs) were inserted. The growth of thin In0.4Ga0.6P insertion layers between In0.49Ga0.51P matrix and InP QD layers reduced the mean height and size fluctuation and significantly improved the uniformity of InP QDs. A higher QDs PL intensity, better uniformity and smaller QDs size had been achieved at 2 ML thickness InGaP insertion layer. The PL emission could be observed around 780 nm red spectral range. There was no blue-shift with increase of the In0.4Ga0.6P insertion layer thickness.